2022
DOI: 10.1149/10701.19001ecst
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Measurement Uncertainty in Cubic Concrete Compression Testing

Abstract: Concrete blocks are one of the important and vital engineering material in the field of construction. To enhance the quality of the block testing is an essential process. There are several testings available. In this paper, the uniaxial compression testing is done for the sample concrete blocks. For the testing concrete cubic specimen with the phase length of 100 mm is taken. The testing is done physically and the compression strength is studied extensively with the theoretical values. Further, the uncertainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The tensile tests for bamboo sticks were conducted on SANS Electromechanical universal testing machine (UTM) model CMT-4304 based on standard GB/T 1447-2005 "Fiber-reinforced plastics composites. Determination of tensile properties" [37]. The load was applied at a rate of 0.1 mm/s.…”
Section: Materials and Methods 21 Bamboo Sticksmentioning
confidence: 99%
“…The tensile tests for bamboo sticks were conducted on SANS Electromechanical universal testing machine (UTM) model CMT-4304 based on standard GB/T 1447-2005 "Fiber-reinforced plastics composites. Determination of tensile properties" [37]. The load was applied at a rate of 0.1 mm/s.…”
Section: Materials and Methods 21 Bamboo Sticksmentioning
confidence: 99%
“…Expanded Uncertainty (U) [4,15,16] The most important aspect of ultrasonic pulse velocity tester is the time measurement, in this study it is observed that in case of uncertainty in time measurement is affected by repeatability transit time measurements, calibration and resolution of instrument. Influence of these parameters is shown in Figure 7.…”
Section: Measurement Uncertainty In Dynamic Young's Modulus Of Elasti...mentioning
confidence: 99%
“…Several measurements are taken on the instrument in a continuous fashion without re-calibration, which can lead to considerable temperature-related uncertainties. The density and Young's modulus of test specimen changes with change in temperature, thus a theoretical calculation can be employed to calculate the wave velocity for a wide range of temperatures (13)(14)(15)(16)(17)(18) . https://www.indjst.org/…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the measurement result is merely known as an approximation of the measurand's value, and it is only completed after combining the uncertainty with final obtained result. This is because all measurements are subject to the errors, it is adequately and frequently claimed that a measurement result outcome is only complete if it is accompanied by a quantitative description of its uncertainty (3,4) . Measurement uncertainty also describes how genuinely the true value of the measur and is known, assuming that no undiscovered systematic errors are impacted by the measurement.…”
Section: Introductionmentioning
confidence: 99%